2017
DOI: 10.1186/s12885-017-3451-x
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter survey of first-line treatment patterns and gene aberration test status of patients with unresectable Stage IIIB/IV nonsquamous non-small cell lung cancer in China (CTONG 1506)

Abstract: BackgroundIn recent years, systemic chemotherapy and molecular targeted therapy have become standard first-line treatments for locally advanced or metastatic nonsquamous non-small cell lung cancer (NSCLC). The objective of this survey was to investigate first-line anticancer treatment patterns and gene aberration test status of patients with advanced nonsquamous NSCLC in China.MethodsPatients included in this study had unresectable Stage IIIB/IV nonsquamous NSCLC and were admitted during August 2015 to March 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
21
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 24 publications
6
21
3
Order By: Relevance
“…According to data from the CTONG 1506 multicenter survey, tobacco consumption is also negatively associated with EGFR mutations. EGFR mutation rates in never, former, and current smokers are reported as 54.4%, 36.0%, and 30.6% ( P < 0.001), respectively . Our study further confirmed the association between these factors and the presence of sensitive del19 and L858R mutations.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…According to data from the CTONG 1506 multicenter survey, tobacco consumption is also negatively associated with EGFR mutations. EGFR mutation rates in never, former, and current smokers are reported as 54.4%, 36.0%, and 30.6% ( P < 0.001), respectively . Our study further confirmed the association between these factors and the presence of sensitive del19 and L858R mutations.…”
Section: Discussionsupporting
confidence: 83%
“…EGFR mutation rates in never, former, and current smokers are reported as 54.4%, 36.0%, and 30.6% (P < 0.001), respectively. 23 Our study further confirmed the association between these factors and the presence of sensitive del19 and L858R mutations. Late N and M stage, and brain metastasis were also independent predictive factors of TKI-sensitive mutations, consistent with the adverse influence of EGFR on patient prognosis.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…However, recent a multicenter survey of stage IIIB/IV NSCLC in China showed that chemotherapy was still the most common first‐line regimen (72.5%), but pemetrexed plus platinum was predominant (70.2%); the detection rate of EGFR gene mutation was 71.4% and the positive rate was 46.5%. Furthermore, 66.3% of patients with positive EGFR gene mutation were treated with EGFR‐tyrosine kinase inhibitors . This shows the treatment model in China has changed in recent years.…”
Section: Introductionmentioning
confidence: 99%